Towards a Knowledge Recipe for State Corporations in the Financial Sector in Kenya - Moturi, Humphrey; Kwanya, Tom; Chebon, Philemon (International Journal of Knowledge Content Development & Technology, 2020)
Knowledge recipes are packages of knowledge which arise from the process of combining the knowledge assets in the organisation in distinctive ways. This involves converting them into useful outputs which are the ideal core competitive advantage enablers for companies. The major objective of this study was to propose a knowledge recipe for financial-sector state corporations in Kenya. The study adopted a convergent parallel mixed methods research design. Quantitative and qualitative data was collected using questionnaires and key informant interviews. The target population of the study was 1574 respondents drawn from all financial state corporations. Multistage sampling technique was used for the study. The first phase involved purposive sampling of the organisations to be studied whereby the four (4) state corporations namely: Capital Markets Authority, Competition Authority of Kenya, Kenya Investment Authority, and Kenya Revenue Authority were identified. The second phase entailed stratified sampling of the respondents in three strata namely senior management team, knowledge management team and general staff. The authors used a census of all senior management team and knowledge management staff while simple random sampling technique was used for the general staff. By use of the Krejcie and Morgan table, the actual sample size was 358 respondents from all the four organisations. Data was collected using questionnaires and interview schedules. The qualitative data was analysed using content analysis while the quantitative data was analysed by the use of Ms. Excel and VOSviewer and presented using pie charts, bar graphs and tables. The response rate for this study was 257(72%). The study revealed that while most employees in the financial sector organisations understand their knowledge needs, knowledge types, knowledge uses and knowledge gaps, they do not have a universal knowledge recipe to facilitate effective knowledge management in their organisations. Consequently, the authors propose a universal knowledge recipe for the state corporations in the financial sector in Kenya. The sets/ingredients of the recipe are: legal knowledge (18%), financial knowledge (15%), administrative knowledge (11%), best practice (10%), lessons learnt (8%), human resource knowledge (8%), research and statistics knowledge (7%), product knowledge (6%), policy and procedure knowledge (5%), ICT knowledge (4%), investor knowledge (3%), markets knowledge (2%), general knowledge (2%) and regulatory framework knowledge (1%). URL: http://ijkcdt.net/xml/24905/24905.pdf